What is the best way to support patients undergoing radiation therapy? - Halkett, Georgia; O'Connor, Moira (John Wiley & Sons, 2015)
This editorial explores ways of providing support to patients undergoing radiation therapy. We highlight the importance of preparing patients and their families for radiation therapy. We also emphasise that patients with children need to be supported and be given advice on communicating with their children. Survivorship and treatment follow-up are also discussed.